New solid surface fluorescence methodology for lead traces determination using rhodamine B as fluorophore and coacervation scheme: Application to lead quantification in e-cigarette refill liquids - Talio, María Carolina (2015)
A new environmental friendly methodology based on fluorescent signal enhancement of rhodamine B dye is proposed for Pb(II) traces quantification using a preconcentration step based on the coacervation phenomenon. A cationic surfactant (cetyltrimethylammonium bromide, CTAB) and potassium iodine were chosen for this aim. The coacervate phase was collected on a filter paper disk and the solid surface fluorescence signal was determined in a spectrofluorometer. Experimental variables that influence on preconcentration step and fluorimetric sensitivity have been optimized using uni-variation assays. The calibration graph using zero th order regression was linear from 7.4×10−4 to 3.4 μg L−1 with a correlation coefficient of 0.999. Under the optimal conditions, a limit of detection of 2.2×10−4 μg L−1 and a limit of quantification of 7.4×10−4 μg L−1 were obtained. The method showed good sensitivity, adequate selectivity with good tolerance to foreign ions, and was applied to the determination of trace amounts of Pb(II) in refill solutions for e-cigarettes with satisfactory results validated by ICP-MS. The proposed method represents an innovative application of coacervation processes and of paper filters to solid surface fluorescence methodology.